Investigating the role of the mPGES-PGE₂-EP4 pathway in Escherichia coli-induced mastitis in dairy cows: insights for non-antibiotic therapeutic strategies - Yang, Xiaolin; Li, Xueqiang; Guo, Lili; Gong, Pengfei; Qian, Yinghong; Zhang, Shuangyi; Liu, Bo; Guo, Wenrui; Bao, Haixia; Mao, Wei (Frontiers in Veterinary Science, 2025)
Escherichia coli (E. coli) is the primary causative agent of bovine mastitis. Currently, antibiotic therapy remains the cornerstone of mastitis treatment; necessitating the identification of alternative therapeutic options. This study employed in vitro cultured bovine bone marrow-derived macrophages (BMDMs) to systematically assess the potential of microsomal prostaglandin e synthase-1 (mPGES-1) inhibitors (MF63, MK886) and EP4 receptor inhibitor (Grapiprant) in modulating inflammatory responses and reducing tissue damage. Cells were pre-treated with mPGES-1 inhibitors and an EP4 receptor inhibitor before infection with E. coli. Following infection, extracellular bacteria were removed, and assays—including ELISA, Western blot, and qRT-PCR—were conducted to analyze inflammatory mediators, protein expression, and gene expression. E. coli infection significantly induced PGE₂ synthesis in BMDMs, which exacerbated the inflammatory response and tissue damage via NF-κB and MAPK signaling pathways, elevating TNF-α, IL-1β, IL-6, and IL-8. Treatment with MF63, MK886 and Grapiprant effectively reduced PGE₂ levels, inhibited NF-κB and MAPK signaling pathways, decreased inflammatory mediators, and enhanced macrophage bactericidal activity, thereby demonstrating potent anti-inflammatory and immunomodulatory effects. Moreover, inhibition of the mPGES-PGE₂-EP4 signaling pathway was found to reduce the expression of damage-associated molecular patterns (HMGB-1 and HABP-2), suggesting alleviation of E. coli-induced tissue damage. Based on the role of PGE₂ in mediating immune and inflammatory responses via the EP4 receptor, inhibiting the mPGES-1-PGE₂-EP4 signaling axis to reduce inflammation and tissue damage will facilitate further investigation into the regulatory mechanisms of the PGE₂ signaling axis in the pathogenesis of mastitis. This approach provides a theoretical foundation and experimental basis for the development of alternative anti-inflammatory therapies to replace antibiotics.